Hazard Identification And Risk Assesment (HIRA) Pada Proses Riksa Uji Mesin Crimping Semi-Otomatis - Rahman Hakim; Dety Febrianti; Mutiarani Mutiarani; Annisa Fyona; Mega Gemala; Nur Fitria Pujo Leksonowati; Hanifah Widiastuti; Benny Haddli Irawan; Auliana Diah Wilujeng (Politeknik Negeri Batam, 2023)
Every phase of work activities in a workplace is inevitably associated with potential hazards and risks that can lead to both workplace accidents and occupational illnesses. To mitigate these hazards effectively, the identification and assessment of risks are imperative, providing a foundation for offering constructive recommendations to the respective companies. The process of hazard identification and risk assessment adheres to the risk management stages, aligned with the AS/NZS 4360:2004 standard on Risk Management, encompassing the determination of consequences (severity) and probability levels (likelihood) to ascertain the risk levels within each work process phase. Upon establishing these risk levels, comprehensive recommendations for control programs can be devised, aimed at averting workplace accidents and occupational diseases. Data acquisition is carried out through surveys/observations involving workers and document reviews. The observations were conducted within the production area, specifically focusing on the semi-automatic crimping machine inspection process at PT. SWS in December 2022. The research findings reveal that within the crimping machine inspection process, the risk percentages are distributed as follows: 0% at the extreme risk level, 65% at the high risk level, 35% at the moderate risk level, and 0% at the low risk level. Effective control and supervision measures are essential to prevent the occurrence of workplace accidents and occupational illnesses. These measures offer significant benefits, encompassing enhanced work productivity, improved work morale, and a fortified corporate reputation. The researcher proposes a range of control measures, spanning substitution, engineering, administrative adjustments, and personal protective equipment provisioning.